An unusual white dwarf star may be a surviving remnant of a subluminous Type Ia supernova - Vennes, S.; Nemeth, P.; Kawka, Adela; Thorstensen, J.; Khalack, V.; Ferrario, L.; Alper, E. (The American Association for the Advancement of Science, 2017)
Subluminous Type Ia supernovae, such as the Type Iax–class prototype SN 2002cx, are described by a variety of models such as the failed detonation and partial deflagration of an accreting carbon-oxygen white dwarf star or the explosion of an accreting, hybrid carbon-oxygen-neon core. These models predict that bound remnants survive such events with, according to some simulations, a high kick velocity. We report the discovery of a high proper motion, low-mass white dwarf (LP 40-365) that travels at a velocity greater than the Galactic escape velocity and whose peculiar atmosphere is dominated by intermediate-mass elements. Strong evidence indicates that this partially burnt remnant was ejected following a subluminous Type Ia supernova event. This supports the viability of single-degenerate supernova progenitors.